An observational study of the endothelial dysfunction in type 2 diabetes mellitus and its association with risk factors - Kesar Vinodbhai Prajapati; Archana U Gandhi; Malay Mukeshbhai Rathod; Mihir Hareshkumar Patel; Savan Patel; Tapan Patel (Wolters Kluwer Medknow Publications, 2022)
Background: Cardiovascular diseases (CVDs) are the major culprit to cause morbidity in type 2 diabetes mellitus (T2DM) patients. Endothelial dysfunction (ED) precedes the progressed stage of CVD presentation. This study aimed to study the risk factors for ED and identify the modifiable factors for risk reduction and provide caution measures. Materials and Methods: This cross-sectional observational study included 100 adult patients with T2DM on oral hypoglycemic drugs or insulin therapy. Based on glycemic control, type 2 diabetic patients were divided into four groups: Group 1 (poor glycemic control and hemoglobin A1C (HbA1c) >9%), Group 2 (fair glycemic control and HbA1c 8%-8.9%), Group 3 (good glycemic control and HbA1C 7-7.9%), and Group 4 (excellent glycemic control, HbA1C <7%). P < 0.05 was considered statistically significant. Results: Overall, significantly higher glycemic levels (fasting blood glucose, postprandial blood glucose, and HbA1c) and lipid derangements (cholesterol, low-density lipoprotein, and triglyceride) were found in patients with ED as compared to those without ED (P < 0.05). Baseline brachial artery diameter (D1) was into three groups, one group with D1 (≤3.6 mm) with mean flow-mediated dilatation (FMD) of 9.07%, Another group of D1 (3.61 mm to ≤4.30 mm) with mean FMD of 5.26%, and the third group with D1 (>4.41 mm) with mean FMD of 4.58%. There was a statistically significant association seen between baseline brachial artery diameter and FMD (P < 0.05). Multivariate linear regression showed that HbA1c and treatment of both Oral hypoglycemic agents (OHA) and insulin were the significant independent factors affecting the ED with OR of 7.566 (P = 0.0003) and 0.013 (P = 0.011), respectively. Conclusion: In diabetics, the risk of ED is increased with worsening levels of lipid profile and glycemia irrespective of the age and duration of the disease.